Caracterização e análise dos acidentes de barragens de rejeito de mineração no estado de Minas Gerais - LIMA, Sarah Ramos de Sousa (2019)
The state of Minas Gerais, it leads the mineral production in what concerns already the quantity and diversity minerals the some decades. However, this production leadership brings also the responsibility for the generation of great quantity of damming originating from his processing factory. The disposal of these wastes as well as maintaining their containment structures is a problem for mining, since generate costs even with the discontinuance of. In this work, are discussed the main constructive models of tailings dam, as well as his functioning. These structures of damming, when not properly constructed and managed, become potential sources of risk, in case of break, bring great economic, social and environmental damage, especially if they are located close to water sources, urban or conservation areas. In Minas Gerais, until now, six accidents took place with dams and, according to the State Foundation of Environment (FEAM), if no action is taken this number may increase, since 19 other dams in the state have unstable structures. In this scenery, the present study is of extreme relevance, as soon as, it characterizes and it analyses the factors that contributed so that these accidents occurred, provided an understanding of the facts, which can be employed in order to prevent further accidents. The six cases of rupture that occurred in the state are presented as a case study. At the end we held a joint analysis of the facts, showing that environmental liabilities caused by mining in Minas Gerais, should be remembered as a legacy of the lack of security and risk management by the sector entrepreneurs, together with legislation which is currently being revised and inefficient supervision.